Effects of Plyometric Training with Agility Ladder on Physical Fitness in Youth Soccer Players - Padrón-Cabo, Alexis; Lorenzo-Martínez, Miguel; Pérez-Ferreirós, Alexandra; Costa, Pablo B.; Rey, Ezequiel (International Journal of Sports Medicine, 2021)
The aim of this study was to assess the effects of plyometric training with an agility ladder on components of physical fitness in youth soccer players. A total of twenty male under-13 soccer players were randomly assigned to a plyometric training group with an agility ladder (n=10) or a control group (n=10). Before and after training intervention linear sprint test (5 m, 10 m, 20 m), vertical jump ability (squat jump, countermovement jump and countermovement jump with arms), agility test, and slalom dribble test were assessed. The plyometric training with agility ladder was applied two times per week over six weeks. Data were analyzed using linear mixed model. The plyometric training group showed significant improvements (p<0.001) from pre-test to post-test in countermovement jump, countermovement jump with arms, and slalom dribble test. In the control group, no significant enhancements were obtained in all performance tests (p>0.05). The between-group analysis showed significant differences in countermovement jump with arms (p=0.03), but no significant differences (p>0.05) were found in squat jump, countermovement jump, sprint, agility test, and slalom dribble test. In conclusion, the short-term plyometric training with agility ladder seems to be ineffective and not time-efficient to improve physical fitness in youth soccer players. However, the interpretation of these results must be understood within the sample size limitations.
Keywords: stretch-shortening cycle; explosive strength; football; team sports